The impact of diferences in plasma glucose between glucose oxidase and hexokinase methods on estimated gestational diabetes mellitus prevalence - Dickson, Lynnsay M.; Buchmann, Eckhart J.; Janse Van Rensburg, Charl; Norris, Shane A. (Nature Research, 2019)
We evaluated the extent of measurement discordance between glucose oxidase and hexokinase laboratory methods and the efect of this on estimated gestational diabetes mellitus (GDM) prevalence in a routine clinical setting. 592 consecutive urban African women were screened for GDM. Paired venous specimens were submitted to two independent calibrated laboratories that used either method to measure plasma glucose concentrations. World Health Organisation diagnostic criteria were applied. GDM prevalence determined by the glucose oxidase and hexokinase methods was 6.9% and 5.1% respectively. The overall GDM prevalence was 9%. Only 34% of GDM positive diagnoses were common to both laboratory methods. Bland Altman plots identifed a bias of 0.2mmol/l between laboratory methods. Plasma glucose concentrations measured by the glucose oxidase method were more platykurtic in distribution. Low diagnostic agreement between laboratory methods was further indicated by a Cohen’s kappa of 0.48 (p<0.001). Reports of GDM prevalence using either the glucose oxidase or hexokinase laboratory methods may not be truly interchangeable or directly comparable.
Keywords: Plasma glucose; Glucose oxidase method; Glocose hexokinase method; Gestational diabetes mellitus; Gestational diabetes; Translational research; SDG-3: Good health and well-being